A Multi-objective Flexible Planning Method for Distribution Network Considering Total System Cost. Issue 1 (1st December 2022) - Li, Yizheng; Peng, Dong; Wang, Xueying; Zhao, Lang; Xue, Yawei
Abstract : In the flexible planning for distribution networks considering distributed generations, a reasonable planning scheme can improve the flexibility of the distribution network concerning the integration of new energy and keep the system running in a stable and reasonable interval. A multi-objective flexible constrained planning method for distribution networks is proposed. Firstly, a multi-objective flexible constrained programming model considering the expectation of cost regret, the expectation of outage loss, and the load balance of the source network is established. Then, the uncertainty of wind turbine output, photovoltaic output, and load is quantified by the scene method and solved by the improved multi-objective discrete particle swarm optimization algorithm. Finally, the distribution network frame is designed for a certain area, and the optimal scheme is obtained by comparing the results of single-objective and multi-objective planning methods. The results prove the superiority of this method, which can improve the overall operation and management level of the distribution network.